Tradition of Resolving Crimes in Kinship Approaches (Tudang Sipulung) Criminal Law and Local Culture in the Community of Balangtaroang Village, Bulukumba Regency, South Sulawesi Province - Rahman Syamsuddin; Achmad Alfian Mujahid (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2023)
This study discusses the encountering between criminal law and local culture in the Balangtaroang Village. It will be discussed through two research questions: How is the construction of crime settlement through the kinship approach (tudang sipulung) in Balangtaroang Village, How is the encountering between criminal law and local culture in resolving criminal acts in a family way in the Balangtaroang Village community. This study is descriptive research using qualitative data obtained through field research. Data collection is carried out through observation in-depth-interview, and documentation. The data obtained will be analysed through legal and sociological approaches. This study argues: that first, crime settlement through kinship approaches is used as one of the ways to solve the case in order to create harmony in the community within the village. Second, crime settlement through kinship approaches is conducted by way of discussion (musyawarah) in a traditional local institution.